Sistem Pengelolaan Sampah Yang Berkelanjutan Di Dinas Lingkungan Hidup Dan Kehutanan Kabupaten Sinjai - Hermansyah; Rajamemang; vivi alvionita (Jurnal Ilmu Administrasi Negara, 2025)
Sustainable Waste Management System at the Department of Environment and Forestry of Sinjai Regency, supervised by Hermansyah (Supervisor I) and Rajamemang (Supervisor II). The Department of Environment and Forestry (DLHK) of Sinjai Regency plays a crucial role in the waste management system in the region. This study aims to analyze the waste management system implemented by DLHK and identify the supporting and inhibiting factors in achieving sustainable waste management. This research employed a qualitative approach through in-depth interviews, direct observation, and document analysis. The analysis focused on five main aspects: operational technical, institutional, financing, legal, and community participation. Research shows that the waste management system in Sinjai Regency still faces several challenges. In terms of operational technical aspects, there is a limited number of waste collection vehicles and TPS 3R facilities that are not functioning properly. In terms of institutional structure, the organization is in place but lacks expert staff and training. Regarding funding, the allocated budget tends to decrease every year and is not enough to cover all waste management activities. From a legal perspective, there are regulations in place, but their implementation is not consistent. On the community participation side, awareness and involvement in sorting waste and maintaining cleanliness remain low. However, there are some supporting factors such as leadership commitment, the existence of local regulations, and the government's efforts in providing basic facilities. This study recommends strengthening waste management policies, increasing human resource capacity, and encouraging community participation to establish a sustainable waste management system.